Experiences of teachers and students on school closures and its consequences during the COVID-19 pandemic in Nyarugusu refugee camp, Tanzania. - Elizabeth H Shayo; Godfrey Mubyazi; Vivien Barongo; Mtumwa Bakari; Zenais Kiwale; Camilla Fabbri; Ellen Turner; Katherine Rodrigues; Karen Devries (Public Library of Science (PLoS), 2024)
Tanzania has experienced several waves of COVID-19 since it was first detected in the country. During the first wave, Tanzania took several measures to prevent wider virus transmission with school closures being one of them. All areas and institutions were targeted, including the refugee camps in Kigoma region. Despite the abundant evidence generated in relation to the effects of the pandemic and associated school closures globally, there has been a paucity of literature exploring the experiences of teachers and students in humanitarian settings. We conducted a qualitative study to explore COVID-19 related school closures in Nyarugusu refugee camp. We aimed to describe teachers' and students' experiences and perceived consequences of school closures. In-depth interviews with teachers and students were conducted in September 2020 in Burundian and Congolese schools in the context of a cluster randomised trial of EmpaTeach, a school-based violence prevention intervention. A total of 44 individuals (29 teachers and 15 students) were interviewed. A phenomenological theoretical framework was used to guide the content analysis. Findings indicated that the COVID-19 pandemic was generally seen as frightening by refugees. Study participants understood the importance of school closures to prevent transmission of the virus, but various negative consequences were reported by both teachers and students. These included perceived mental health difficulties such as stress, depression and anxiety associated with the worry of infection, idleness, and disruption of education. Participants also perceived an increase in occurrences of early marriages and unplanned pregnancies, which they thought contributed to increased school dropout. Participants identified the main causes of such outcomes as a lack of parental supervision, children's lack of restraint and poor character, and a lack of alternative teaching practices (such as online or remote learning) to keep the students busy while at home. Children were held accountable for their faults with little support from the adults. Our findings suggest that there is an urgent need to strengthen child protection programming to support children and their communities during emergencies and provides protective environments such as school and education. There is a critical need to develop preparedness plans for future pandemics to support child safety, academic development and wellbeing.